Analysis and characterization of roping in AA6XXX automotive sheet. Issue 1 (1st December 2022) - Hu, Y; Yuan, X; Zhou, G; Cao, L; Yang, B; Li, D
Abstract : Roping is a severe surface defect in aluminium alloy sheets that can affect the product's surface quality. However, quantitative prediction of roping is still a challenge. This paper introduces an approach combining experiment and simulation to analyse the roping phenomenon quantitatively in aluminium alloy sheets. A white light interferometer is employed to acquire large-area surface morphology with a detailed description of the corresponding morphological image preprocessing method. The electron backscatter diffraction (EBSD) mapping is conducted on the surface of the two sheets with different roping intensities to acquire orientation maps, and the crystal plasticity framework is developed to predict thickness strain after uniaxial tension. To obtain the quantitative roping prediction, a scaling parameter is proposed to map the predicted thickness strain to the actually measured height variance in depth.